The evolution of global standards of accounting - Günther Gebhardt (Goethe University Frankfurt, Center for Financial Studies (CFS), 1999)
The globalization of markets and companies has increased the demand for internationally comparable high quality accounting information resulting from a common set of accounting rules. Despite remarkable efforts of international harmonization for more than 25 years, accounting regulation is still the domain of national legislators or delegated standard setters. The paper starts by outlining the reasons for this state of affairs and by characterizing the different institutional backgrounds of accounting standard setting in four selected countries as well as on the international level. This is followed by a summary of important international differences in accounting rules and a summary of the empirical evidence of the impact of different rules on the resulting numbers and their relevance to users. It is argued that neither a priori theoretical reasoning nor the evidence from empirical studies provides a convincing basis for choices between accounting regimes and even less so between specific accounting rules. As there is a broad consensus that there is a need for one set of global accounting standards the final sections of the paper discuss currently existing and proposed structures of international accounting standard setting. The evolving new IASC structure is critically evaluated.
urn:nbn:de:hebis:30-9700
Keywords: G10; G15; G18; 330; Standard Setting; Global Accounting Standards; Accounting regulation; IASC New Structure